Kekerabatan Bahasa Nafri, Sentani, dan Tabla: - Yohanis Sanjoko (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
This research aims to find the relation between Nafri, Sentani, and Tabla language. The researcher used lexicostatistical approach. Lexicostatistics is a technique in which language groupings tend to promote observation of words (lexicon) statistically. Through this technique, it is then possible to draw conclusion based upon similarity percentage and differences between one language and another. The results showed that Nafri, Sentani, and Tabla language come from one language family.